A concise one-step synthesis of primin and iso-primin. Issue 17 (22nd April 2015) - Nasiri, Hamid R.; Ferner, Jan; Tükek, Caner; Krishnathas, Robin; Schwalbe, Harald
Graphical abstract: Abstract: A short, efficient one-step synthesis of primin and its isomer is devised. The synthesis is based on the introduction of an alkyl side chain via radical alkylation of 2-methoxy-benzoquinone. The required alkyl radical was either generated from the corresponding alkyl acid or alkyl boronic acid in the presence of persulfate under silver catalysis. The alkylation of 2-methoxy-benzoquinone occurs at the C-6 and C-5 position, generating the desired primin and iso-primin. The formation of the natural product primin was confirmed by NMR spectroscopy determining carbon–carbon constitution at 13 C natural abundance in an 1, 1-ADEQUATE experiment.